IMPROVING AND INCREASING THE EFFICIENCY OF THE SYSTEM OF CONTINUOUS SPIRITUAL EDUCATION IN THE RENEWED UZBEKISTAN - Rakhmanov Utkirbek Usmonjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In work is analyzed existing system of the unceasing education Uzbekistan, as well as the policy on reform spheres of education, as the key of area, conducted course of the reforms and renovations society, as necessities and obligatory condition of the democratic transformations in-the country, firm development of the economy, integrations of the republic in the world community.